The protective effect of sunscreens against ultraviolet B-induced immunosuppression. A study on Langerhans cell depletion - Flora Ramona SP Fajar Waskito Yohanes Widodo Wirohadidjojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2010)
Ultraviolet B (UVB) radiation can act as immunosuppressant by inducing an epidermal Langerhans cells (LC) depletionwhich could be inhibited by topical sunscreen. Several kinds of sunscreens with various SPF (Sunscreen ProtectionFactor) are now available. The minimal SPF which able to inhibit the immunosuppressive effect of UVB amongpeople with skin photo-type IV has not been established yet. The aim of this study is to determine the minimal SPFcapable to inhibit UVB-induced immunosuppression among people with skin photo-type IV. A simple experimental(post test only experimental) study was conducted among 5 people’s circumsized foreskins with Fitzpatrick’s skinphoto-type IV. Each of them was divided into equal 5 pieces of 0.5 cm2. Each of three pieces of skin was treated bysunscreen SPF 15, SPF 30, and SPF 50, a single piece of skin was treated with placebo, and all of them then weretreated by a single 100 mJ/cm2 of UVB 30 minutes later. A rest single piece of skin was used as control. After 24hours of incubation in incubator of 37O C and 5% CO2, all of them then was fixed by buffer formalin, blocked byparaffin, cut in 2mm of thickness, and then stained with anti CD 1a antibody with AEC as chromogen and Mayer’shematoxylin as counterstaining. The number of LC was counted by Image J Analysis programmed and the mean ofLCwere analyzed by Kruskal-Wallis test dan Mann-Whitney test. There were very significantly different of themean number of LC between UVB placebo group and control group (p < 0.01). Compared to the control group,mean number of LC among SPF 30 and SPF 50 treated groups were not significantly different (p>0.05). Sunscreenwith SPF 15 had LC number lower than control group significantly (p<0.05). The lowest SPF for preventing UVBinduced LC depletion among people with skin photo-type IV was 30.Key words : UVB - immunosupression – sunscreens – SPF -CD1aexpression